Perancangan Departemen Teknis untuk Perawatan Mesin Di PT X - Flynn Flynn; Felecia Felecia (Jurnal Titra, 2021)
PT X is a growing company and still does not have a department to carry out engine maintenance. Machine maintenance is still carried out when the machine is damaged. Implementing machine maintenance is still carried out by the production department so that the production department cannot focus on production activities. The technical department is designed to maintain the stability of machine performance and support production activities. The design of the technical department as the responsible department of machine maintenance is carried out by conducting interviews with technical supervisors and technicians who carry out the machine maintenance process. The results of the interviews were then processed and made into various requirements for the formation of a technical department. The design of the technical department as the person in charge of machine maintenance is carried out so that the company can have data on the cycle of damage to machine components, spare parts used and expenses incurred for machine repair. The results of the technical department design include departmental structures, job descriptions, machine maintenance process flows, data collection documents, SOPs and work instructions as well as technical department reports. This can support the company in the engine maintenance process and data collection on the use of spare parts for the engine repair process.